Limited health literacy increases the risk of frailty among community‐dwelling older adults: Longitudinal findings from the Korean Frailty and Aging Cohort Study. Issue 4 (9th March 2022) - Choi, Eun Young; Shin, Heyri; Kim, Sukyung; Lee, Hee Yun; Kim, Young Sun
Abstract : Aim: Despite the growing recognition of the importance of health literacy, there is a lack of knowledge on the longitudinal association between health literacy and frailty. The present study explored whether limited health literacy increases the risk of developing pre‐frailty and frailty among older adults. Methods: Data were drawn from the Korean Frailty and Aging Cohort Study, a nationwide, population‐based prospective cohort study of community‐dwelling older Koreans. A baseline sample of 2808 adults aged 70–84 years was analyzed for the cross‐sectional models, and 2278 participants in the 2‐year follow‐up assessment were included for the longitudinal analyses. Multinomial logistic regression models were used to evaluate the relative risk ratios of pre‐frailty or frailty, where a robust group served as the reference category. Results: The findings showed that baseline limited health literacy was associated with an approximately 1.4‐fold increased risk of developing pre‐frailty after 2 years, even after adjusting for sociodemographic characteristics, health behaviors and health status. However, the longitudinal association between health literacy and frailty was not significant after adjusting for health‐related factors. Conclusions: Our findings point to the importance of promoting health literacy among older adults, and provide preliminary evidence that can inform the development of tailored public health strategies. Geriatr Gerontol Int 2022; 22: 325–331 .